Laboratory investigation into the effects of fibres and bituminous emulsion on cement-treated recycled materials for road pavements. Issue 7 (8th August 2016) - Toraldo, E.; Mariani, E.; Crispino, M.
Abstract : The laboratory investigation described in this paper focuses on the effects of fibres and bituminous emulsion (BE) on cement-treated recycled materials (CTMs) for road pavements. To this purpose, the investigation was carried out in two phases. The first one aimed at defining the mechanical performances of a CTM containing two types of fibres, of two different lengths. On the basis of the results obtained during the first phase, phase two focused on the evaluation of the mechanical effects of curing and in-service temperatures on both the CTMs studied in the first phase and the same CTMs treated using a BE. Results showed that fibres increase CTMs' performance at in-service temperatures, whereas an increase of CTMs' viscoelastic characteristics occurs when BE is used.